Aetiology and factors associated with bacterial diarrhoeal diseases amongst urban refugee children in Eastleigh, Kenya: A case control study - Waqo G. Boru; Gideon Kikuvi; Jared Omollo; Ahmed Abade; Samuel Amwayi; William Ampofo; Elizabeth T. Luman; Joseph Oundo (AOSIS, 2013)
Introduction: Kenya is home to over 400 000 refugees from neighbouring countries. There is scanty information about diarrhoea amongst urban refugees in Kenya. Objectives: We investigated the enteric bacteria causing diarrhoea amongst urban refugee children and described the associated factors. Method: During the period of August-December 2010, urban refugee children between the ages of two and five who attended Eastleigh County Council Health Centre were enrolled into the study. Diarrhoeal cases were compared with age-matched children with no diarrhoea (controls). Stool specimens were collected and enteric bacteria isolated. A questionnaire was administered to identify risk factors. Results: A total of 41 cases and 41 controls were enrolled in the study. The age and country of origin were similar for cases and controls. The bacterial isolation rates amongst the cases were: non-pathogenic Escherichia coli 71%, Shigella dysenteriae 2.4%, Shigella flexneri 2.4%, Salmonella paratyphi 5%. For the controls, non-pathogenic E. coli 90% and enterotoxigenic E. coli (ETEC)2.4% were amongst the organisms isolated. All isolates were resistant to amoxicillin; resistance to other antibiotics varied by isolate type. Factors associated independently with diarrhoea included children not washing their hands with soap (aOR 5.9, p < 0.05), neighbour(s) having diarrhoea (aOR 39.8, p < 0.05), children not exclusively breastfed for their first 6 months (aOR 7.6, p < 0.05) and children eating food cooked the previous day (aOR 23.8, p = 0.002). Conclusions: Shigella species, Salmonella species and ETEC were found to be responsible for diarrhoea amongst the urban refugee children. Measures to control and guide the use of antibiotics are critical for the prevention of antibiotic resistance. Efforts to improve personal and domestic hygiene, including educational campaigns to promote appropriate handwashing, should be encouraged.